Residents' Perceptions of Stress Related to Cruise Tourism Development. Issue 4 (2nd October 2017) - Jordan, Evan J.; Vogt, Christine A.
ABSTRACT: Stress is one potential impact that can affect tourism host community residents through tourism development activities. Stress is experienced through an increase in daily hassles, which, with long-term exposure, can result in negative health and behavioral outcomes and decreased quality of life. The community of Falmouth, Jamaica recently hosted development of a new cruise port, and is now one of the busiest ports in the Caribbean. A random sample of Falmouth residents were qualified for a study on stress and then asked to complete a survey. Seventy-eight percent ( n = 362) of survey respondents perceived stress related to development of the new cruise port, while 22% reported no stress. Thematic analysis revealed unmet expectations, crowding/congestion, increased cost of living, pollution, police harassment, displacement, and overused utilities were causes of stress. Post-hoc chi-square tests revealed significant differences in perceived stressors by those with differing levels of education. This research provides insight into an intangible psychological impact of cruise tourism development, one element of host community resident quality of life.